FAKTOR-FAKTOR YANG MEMPENGARUHI GANGGUAN SIKLUS MENSTRUASI MAHASISWI FAKULTAS ILMU KESEHATAN UPN VETERAN JAKARTA PADA MASA PANDEMI COVID-19 - Apriella Warnina Putri, (2021)
Menstruation was a process of reproductive organs that occurs every month in women. The process of menstruation was not always smooth for women. There are three disorders of the menstrual cycle, namely amenorrhea, oligomenorrhea, and polimenorrhea. Menstrual cycle disorders are generally experienced by adolescents and early adults, one of whom is female student. This study aims to determine the factors associated with menstrual cycle disorders in students of the Faculty of Health Sciences at UPN Veteran Jakarta during the COVID-19 pandemic. The design of this study was cross-sectional analytic. The sampling technique was proportionate stratified random sampling with a sample size of 155 respondents. The variables studied were age of menarche, economic status, physical activity, stress, sleep quality, and dietary habit. Bivariate data analysis used chi square test and multivariate data analysis using multiple logistic regression test with α = 0.05. The results in this study indicate that factors associated with menstrual cycle disorders include economic status (p value = 0.040, OR = 0.5), stress (p value = 0.006, OR = 3.8), sleep quality (p value = 0.026 , OR = 2.4), and dietary habit (p value = 0.002, OR = 2.9). Meanwhile the variables that have no relationship is age of menarche (p value=0,308, OR=1,6) and physical activity (p value=0,847, OR=1,3). Based on the results of multivariate analysis, respondents who have severe stress, poor sleep quality, and poor dietary habit have a 1.3 times risk of experiencing menstrual cycle disorders and the variable that has the greatest influence on the menstrual cycle is dietary habit (p value=0,001, OR=3,3). Respondents are expected to live a healthy life, have adequate rest, and manage stress.